RADIOCARBON STUDIES OF ORGANIC COMPOUND CLASSES IN PLANKTON AND SEDIMENT OF THE NORTHEASTERN PACIFIC OCEAN - RESULTS FROM SEDIMENT TRAP EXPERIMENTS - Wang X.C.; Druffel E.R.M.; Griffin S.; Lee C.; Kashgarian M. (My University, 1998)
Radiocarbon (Δ14C) and stable carbon isotopes (δ13C) were measured in total hydrolyzable amino acid (THAA), total carbohydrate (TCHO), total lipid, and acid-insoluble organic fractions that had been separated from phytoplankton, zooplankton, sediment floc, and sediment samples from an abyssal site in the northeastern Pacific Ocean. THAA, TCHO, and lipid fractions accounted for 91-99% of the total organic carbon (TOC) in phytoplankton and zooplankton, 57% of TOC in sediment floc, and 18-38% of TOC in sediment. Based on concentration profiles in sediment, first-order degradation rate constants below the bioturbation zone were calculated using a multi-G model considering both labile and refractory organic fractions. The calculated rate constants were in the order THAA ~ TCHO > TOC ~ TN > lipid, indicating the relative reactivities of these compound classes in the sediment during early diagenesis. Bioturbation affected the distributions of these compound classes in the top few centimeters of the sediment.The Δ14C values of all organic fractions decreased in the order plankton in surface water to sediment floc to sediments at 4100 m depth. Distinct differences in Δ14C exist among THAA, TCHO, and lipid fractions in sediment floc and sediments. The lipid fraction exhibited lower Δ14C signatures than THAA and TCHO fractions. Differential decomposition of organic matter and sorption and/or biological incorporation of 'old' DOC into sediment appear to be the major processes that likely control the observed Δ14C signatures and abundances. δ13C values of the organic compound classes in sediment are similar to their values in plankton indicating that organic matter input to sediment in the northeastern Pacific is mainly from marine sources. Also, distinct δ13C signatures were found in each of the four organic fractions.